Lymphaticovenular anastomosis to prevent cellulitis associated with lymphoedema. Issue 11 (13th August 2014) - Mihara, M; Hara, H; Furniss, D; Narushima, M; Iida, T; Kikuchi, K; Ohtsu, H; Gennaro, P; Gabriele, G; Murai, N
Abstract: Background: One of the complications of lymphoedema is recurrent cellulitis. The aim was to determine whether lymphaticovenous anastomosis (LVA) was effective at reducing cellulitis in patients with lymphoedema. Methods: This was a retrospective review of patients with arm/leg lymphoedema who underwent LVA. The frequency of cellulitis was compared before and after surgery. The diagnostic criteria for cellulitis were a fever of 38·5°C or higher, and warmth/redness in the affected limb(s). Results: A total of 95 patients were included. The mean number of episodes of cellulitis in the year preceding surgery was 1·46, compared with 0·18 in the year after surgery ( P < 0·001). Conclusion: LVA reduced the rate of cellulitis in these patients with lymphoedema. Abstract : Possible treatment for lymphoedema